2019
DOI: 10.1038/s41409-019-0536-y
|View full text |Cite
|
Sign up to set email alerts
|

Prospective phase II study of prophylactic low-dose azacitidine and donor lymphocyte infusions following allogeneic hematopoietic stem cell transplantation for high-risk acute myeloid leukemia and myelodysplastic syndrome

Abstract: Thirty patients, with high-risk acute myeloid leukemia (AML, n = 20) or myelodysplastic syndrome (MDS, n = 10), were enrolled in a phase II trial entailing prophylactic post-transplant azacitidine (AZA) plus escalated doses of donor lymphocyte infusion (DLI). The median number of AZA cycles was 5 (1-12) with 10 patients (33%) completing the 12 projected cycles. DLI were performed in 17 patients: 5 received one DLI, 2 received 2 DLI and 8 received 3 infusions. AZA was well tolerated, but discontinued in 20 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 43 publications
(73 reference statements)
0
48
0
Order By: Relevance
“…Although alloHSCT improves outcomes, the therapeutic benefit of alloHSCT in patients with persistent MRD positivity is only partial, which is mainly due to a high risk of relapse during the first year after alloHSCT. Thus, an effective prophylactic or preemptive therapy in post-transplantation might be important in order to reduce the rate of relapse [14,15,16,17,18]. Moreover, although the relatively small number of patients precludes drawing definitive conclusions, among patients who were MRD-positive after two consolidation cycles, we observed a negative effect of increasing levels of MRD on OS and DFS.…”
Section: Discussionmentioning
confidence: 86%
“…Although alloHSCT improves outcomes, the therapeutic benefit of alloHSCT in patients with persistent MRD positivity is only partial, which is mainly due to a high risk of relapse during the first year after alloHSCT. Thus, an effective prophylactic or preemptive therapy in post-transplantation might be important in order to reduce the rate of relapse [14,15,16,17,18]. Moreover, although the relatively small number of patients precludes drawing definitive conclusions, among patients who were MRD-positive after two consolidation cycles, we observed a negative effect of increasing levels of MRD on OS and DFS.…”
Section: Discussionmentioning
confidence: 86%
“…This will likely increase the predictive value of pretransplant MRD status on relapse risk and OS above what has been observed with MRD positivity as currently ascertained in the EBMT registry database. Further, having these data in the registry will also benefit to study assessing the impact of prophylactic intervention such as posttransplant immunosuppression discontinuation, donor lymphocyte infusion, or targeted low-intensity therapies on leukemia progression [34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies performed in epithelial malignancies demonstrated that HMAs can promote reactivation of dormant human endogenous retroviruses, which, upon transcription, elicit innate immune sensing and induction of adaptive responses (110,111). In addition, azacitidine was shown to improve T cell repertoire in MDS (112), and its efficacy in combination with donor lymphocyte infusion in the post-alloHSCT setting supports azacitidine's ability to induce tumor-specific responses (113)(114)(115).…”
Section: Immunologic Effects Of Common Antileukemia Therapiesmentioning
confidence: 95%